Methodology of thermal resistance and cooling effect testing of green roofs - Tetiana Tkachenko (Songklanakarin Journal of Science and Technology (SJST), 2020)
For the first time, methodological approaches have been developed and given to determine heat exchange processes in the living vegetation layers of green roofs using total thermal resistance, which takes into account the heat exchange processes directly in it and the heat transfer on its free surface. The approaches take into account wind speed. In addition, for the first time, clarification has been made in the understanding of the term “cooling effect”, as the difference of the temperatures between the living plant layer and the air. The method of its determination is proposed. Engineering approach to thermotechnical calculation of the green roofs is given taking into account the “cooling effect”. Influence of the wind speed on the “cooling effect” has been determined. Based on the influence, the recommendations for parapet construction are provided for “cooling effect control” maximizing energy efficiency of buildings.